Construction method of scaffolding design / Nurul Syuhadah Atikah Shamsuddin - Shamsuddin, Nurul Syuhadah Atikah (Universiti Teknologi MARA, Perak, 2015)
Practical training at the project site ' Cadangan Membina Kompleks Ibu Pejabat Majlis Perbandaran Kuantan (MPK), Di atas Lot 29, Seksyen 30, Jalan Tanah Putih, Kuantan, Pahang Darul Makmur under Majlis Perbandaran Kuantan (MPK) gave me a lots of useful information in preparing this project report. This report is regarding about the Method Scaffolding Design Construction to fulfil the requirements set by the Building Department to get Diploma in Buildings. This study produced by observation and my involvement in the construction world for 5 months beginning on 28 october 2013 until 17 march 2014. Explanation in this report is about design specification of scaffolding, types of scaffolding, scaffolding construction methods and thesafety features regarding the use of scaffolding. As conclusion, this report will explain in more detail about scaffolding design m construction methods.